Mechanisms of detoxification of high copper concentrations by the microalga Chlorella sorokiniana. Issue 19 (5th October 2020) - Vojvodić, Snežana; Stanić, Marina; Zechmann, Bernd; Dučić, Tanja; Žižić, Milan; Dimitrijević, Milena; Danilović Luković, Jelena; Milenković, Milica R.; Pittman, Jon K.; Spasojević, Ivan
Abstract : Microalgae have evolved mechanisms to respond to changes in copper ion availability, which are very important for normal cellular function, to tolerate metal pollution of aquatic ecosystems, and for modulation of copper bioavailability and toxicity to other organisms. Knowledge and application of these mechanisms will benefit the use of microalgae in wastewater processing and biomass production, and the use of copper compounds in the suppression of harmful algal blooms. Here, using electron microscopy, synchrotron radiation-based Fourier transform infrared spectroscopy, electron paramagnetic resonance spectroscopy, and X-ray absorption fine structure spectroscopy, we show that the microalga Chlorella sorokiniana responds promptly to Cu 2+ at high non-toxic concentration, by mucilage release, alterations in the architecture of the outer cell wall layer and lipid structures, and polyphosphate accumulation within mucilage matrix. The main route of copper detoxification is by Cu 2+ coordination to polyphosphates in penta-coordinated geometry. The sequestrated Cu 2+ was accessible and could be released by extracellular chelating agents. Finally, the reduction in Cu 2+ to Cu 1+ appears also to take place. These findings reveal the biochemical basis of the capacity of microalgae to adapt to high external copper concentrations and to serve as both, sinks and pools of environmental copper.